Old bilberry forest increases likelihood of Capercaillie Tetrao urogallus lek occupancy in Southern Norway - Gregersen, Håkon; Gregersen, Finn (Ornis Norvegica, 2008)
Capercaillie Tetrao urogallus prefers old forest, and bilberry Vaccinium myrtillus is a key dietary component. This study aimed to explore lek occupancy and size in relation to those habitat qualities (old forest proportion and type), by examining 246 leks situated in south-eastern Norway. Lek occupancy, lek size and proportion old forest/old bilberry forest were estimated within 0.3 and 1 km radius respectively. Our results showed that lek occupancy and size depended strongly on the proportion of old bilberry forest. Other old forest had no effects on lek occupancy or size after accounting for the effects of old bilberry forest. These findings can be implemented in forest management plans to improve lek habitats and population size.